An Overview of Students' Conceptual Understanding in Kinematics Using Computer Based Test (CBT) Class XI SMA Negeri 19 Palembang - Ketang Wiyono; Sudirman Sudirman; Kristylia Sury; Saparini Saparini; Melly Ariska (JIPF (Jurnal Ilmu Pendidikan Fisika), 2021)
This study aims to analyze the category of understanding the concept of kinematics using Certainty of Response Index (CRI) assisted Computer Based Test (CBT) and to determine misconceptions in class XI students of SMA Negeri 19 Palembang. The method used in this research is descriptive and the instrument used in this study is a multiple choice test using CRI and reason. The test was conducted on 57 students from class XI IPA 1 and XI IPA 3. Rasch modeling is used for the processing stage from raw data to logit numbers which will provide information related to infits and outfits in the ministep software besides manual analysis using CRI. The result of the analysis that have been carried out considering students who are outliers or misfits, data from the ministep software and the reasons for the answer given, 41 students are obtained according to the Rasch modeling and 16 students who are outliers or misfits. The result showed that the average score of concept understanding was 23.44%, while for the concept understanding category it was 2.15%, the concept understanding category but not sure was 0.00%, the misconception category was 70.02% and did not understand the concept of 27.83%. The result of the interview found several causes of misconceptions, namely the references form used in the languange in the book was difficult to understand and the learning model usel was not quite right.